Evaluation of the 3M™ Petrifilm™ Rapid Aerobic Count Plate for the Enumeration of Aerobic Bacteria: Collaborative Study, First Action 2015.13. (27th November 2019) - Bird, Patrick; Flannery, Jonathan; Crowley, Erin; Agin, James; Goins, David; Jechorek, Robert; ,
Abstract: The 3M™ Petrifilm™ Rapid Aerobic Count (RAC) Plate is a sample-ready culture medium system containing dual-sensor indicator technology for the rapid quantification of aerobic bacteria in food products. The 3M Petrifilm RAC Plate was compared to the U.S. Food and Drug Administration Bacteriological Analytical Manual (FDA BAM) Chapter 3 (Aerobic Plate Count) for the enumeration of aerobic bacteria in raw easy-peel shrimp and the Standard Methods for the Examination of Dairy Products (SMEDP) Chapter 6 (Standard Plate Count Method) for the enumeration of aerobic bacteria in pasteurized skim milk and instant nonfat dry milk (instant NFDM). The 3M Petrifilm RAC Plate was evaluated using a paired study design in a multilaboratory collaborative study following current AOAC validation guidelines. Three target contamination levels (low, 10–100 CFU/g; medium, 100–1000 CFU/g; and high 1000–10 000 CFU/g) were evaluated for naturally occurring aerobic microflora for each matrix. For raw easy-peel shrimp, duplicate 3M Petrifilm RAC Plates were enumerated after 24 ± 2 h incubation at both 32 and 35°C. Pasteurized skim milk 3M Petrifilm RAC Plates were enumerated after 24 ± 2 h incubation at 32°C, and instant NFDM 3M Petrifilm RAC Plates were enumerated after 48 ± 3 h incubation at 32°C. No statistical difference was observed between 3M Petrifilm RAC Plate and FDA BAM or SMEDP reference methods for each contamination level.